Simulation Investigation on Multiphase Kick Behavior and Kick Tolerance for Highly Deviated Fractured Basement Reservoirs - Sharafaddin, O. (Slovnaft VURUP a.s, 2021)
There are various difficulties involved in drilling operations in the oil and gas industry. Well controlling is considered the most vital one. Therefore, this work investigates and analyses these pressure changes that act on these parameters during well control using Engineer's method. Since fractured basement is an important oil and gas contributor to the petroleum industry, a case study was conducted on a basement reservoir using Drillbench multiphase flow simulator for various kick size and various kick intensity 10, 50, and 80 bbl and 0.1, 1.0, and 1.5 ppg respectively. The sensitivity analysis proved that kick size and kick intensity have significant effect while circulating the kick. The bigger the size of kick the higher pressure profile was noticed. Similarly, an increase in kick intensity would result in increasing choke pressure, casing shoe pressure and pump pressure. Basement reservoirs have bigger kick size due to the high pressurized and fractured network that lead to complicate controlling the well. The obtained results greatly show the importance of defining kick tolerance and assist drilling rig operators to anticipate how dangerous is to underestimate gas kicks and appropriately manage to circulate the gas kick out of the wellbore safely. Â© 2021. All Rights Reserved.